PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KEPUASAN PEGAWAI REKTORAT UNIVERSITAS HALU OLEO - Ariyanti, Yenny; Sarita, Buyung; Maharani, Sriwiyati (Pascasarjana Universitas Halu Oleo, 2019)
This studi aim This study aims: 1) to examine the influence of culture on job satisfaction of employees of the UHO headquarters, 2) to assess compensation for satisfaction with job satisfaction of employees of the UHO headquarters.The object of this research is the Halu Oleo University headquarters. The population of the study was invited civil servants at the Halu Oleo University headquarters consisting of the Civil Service and General Bureau, the Planning and Budgeting Bureau and the Academic and Student Affairs Bureau which was contacted by 137 people. The sample size uses the Slovin formula with 5% precision so the number of research samples won 102 people. Methods of collecting data using questionnaires. The data measurement model is structural thus the research data is analyzed using smartPLS 2.The results of testing the data show the value of R-Square of 0.642, and the results of the study are: 1) positive and significant organizational culture on job satisfaction of UHO rector's employees, 2) positive and significant compensation for job satisfaction of UHO rector's staff.Â Keywords: Organizational Culture, Compensation, Job SatisfactionÂ